THE INFORMATIONAL POWER OF DIVIDEND POLICIES AND THE IMPACT ON THE VALUE OF THE FIRMS IN CHILE - Alejandro Torres Mussatto; Eric Salinas Mayne (European Scientific Journal, ESJ, 2014)
The proposed research shows the informational power that the dividend policies of firms have in the Chilean stock market. For this purpose, the stocks of firms belonging to the main index, the Selective Stock Price Index (IPSA) of the Santiago Stock Exchange, were put into groups considering the percentages of profit sharing of their shareholders. By using the valuation ratios, it is possible to determine the intrinsic values of the shares comprising the index. This leads to the suggestion of purchasing undervalued securities that were undervalued by the market from stocks that reached the highest dividend distribution rates. In addition, they showed that greater dividend rates were preceded by growth rates of large firms. Complementing the results above, the firms that share higher profits to shareholders are those who have property in greater concentration, along with reaching greater yield results than those obtained by firms that spend a smaller percentage of their dividend distribution.